Pharmacomagnetography assessment of the prokinetic effect on metronidazole absorption - Soares, Guilherme Augusto [UNESP]; Rodrigues, Gustavo Serafim [UNESP]; Buranello, Lais Pereira [UNESP]; De Oliveira, Ricardo Brandt; De Arruda Miranda, José Ricardo [UNESP] (Oxford University Press (OUP), 2023)
Objectives: This study aimed to evaluate the effects of prucalopride, a prokinetic agent that acts as a potent serotonin agonist of 5-HT4 receptors, on gastric emptying and small bowel transit and assess its impact on the absorption of metronidazole. Methods: Six healthy volunteers, three men and three women, aged between 20 and 27 years, with a body weight ranging from 50 to 80 kg, were enrolled in this study. The pharmacokinetics and gastrointestinal transit parameters were evaluated simultaneously through pharmacomagnetography assessment, combining alternating current biosusceptometry and blood analysis. Key findings: The results showed that prucalopride enhances gastric emptying and small bowel transit when administered orally and significantly impacts the rate of metronidazole absorption, leading to enhanced bioavailability and rapid therapeutic response. Conclusion: Pharmacomagnetography assessment allows simultaneous tracking of transit by images and is a valuable method for analysing drug absorption using multiple instruments.
Keywords: AC biosusceptometry; gastrointestinal tract; pharmacomagnetograpy; prucalopride